1999
DOI: 10.1002/(sici)1097-0290(19990120)62:2<166::aid-bit6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Increasing extracellular matrix production in regenerating cartilage with intermittent physiological pressure

Abstract: Isolated equine chondrocytes, from juveniles and adults, were cultured in resorbable polyglycolic acid meshes for up to 5 weeks with semicontinuous feeding using a custom‐made system to intermittently compress the regenerating tissue. Assays of the tissue constructs indicate that intermittent compression at 500 and 1000 psi (3.44 and 6.87 MPa, respectively) stimulated the production of extracellular matrix, enhancing the rate of de novo chondrogenesis. Constructs derived from juvenile cells contained concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(80 citation statements)
references
References 55 publications
3
77
0
Order By: Relevance
“…Mechanical signals, such as hydrostatic pressure (HP), are a key component of the in vivo joint environment and have been shown to play a significant role in regulating the chondrogenic differentiation of mesenchymal stem cells. Previous studies have shown varying and occasionally conflicting results (Parkkinen et al, 1993;Carver and Heath, 1999;Suh et al, 1999;Carver and Heath, 2000;Jortikka et al, 2000;Smith et al, 2000Smith et al, , 2005Hu and Athanasiou, 2006;Finger et al, 2007;Ogawa et al, 2009;Meyer et al, 2011;Liu et al, 2012;Maxson and Burg, 2012;Puetzer et al, 2012;Safshekan et al, 2012;Steward et al, 2012;Vinardell et al, 2012a;Steward et al, 2013), but it would appear that the application of physiological levels (3-10 MPa) of intermittent HP can enhance proteoglygan and collagen synthesis and upregulate aggrecan and collagen II mRNA expression in chondrocytes and stem/progenitor cells isolated from bone marrow, synovial tissues and adipose tissues. There is also evidence to suggest that dynamic HP can act to stabilise the phenotype of chondrogenically primed joint tissue derived MSCs (Vinardell et al, 2012a).…”
Section: Introductionmentioning
confidence: 74%
“…Mechanical signals, such as hydrostatic pressure (HP), are a key component of the in vivo joint environment and have been shown to play a significant role in regulating the chondrogenic differentiation of mesenchymal stem cells. Previous studies have shown varying and occasionally conflicting results (Parkkinen et al, 1993;Carver and Heath, 1999;Suh et al, 1999;Carver and Heath, 2000;Jortikka et al, 2000;Smith et al, 2000Smith et al, , 2005Hu and Athanasiou, 2006;Finger et al, 2007;Ogawa et al, 2009;Meyer et al, 2011;Liu et al, 2012;Maxson and Burg, 2012;Puetzer et al, 2012;Safshekan et al, 2012;Steward et al, 2012;Vinardell et al, 2012a;Steward et al, 2013), but it would appear that the application of physiological levels (3-10 MPa) of intermittent HP can enhance proteoglygan and collagen synthesis and upregulate aggrecan and collagen II mRNA expression in chondrocytes and stem/progenitor cells isolated from bone marrow, synovial tissues and adipose tissues. There is also evidence to suggest that dynamic HP can act to stabilise the phenotype of chondrogenically primed joint tissue derived MSCs (Vinardell et al, 2012a).…”
Section: Introductionmentioning
confidence: 74%
“…Cyclic compressive loading on articular cartilage enhances chondrocyte biosynthetic response and extracellular matrix production. [32][33][34][35][36][37] Moreover, cyclic compressive loading has chondroprotective effects. It inhibits the release of matrix metalloproteinase and proinflammatory mediators, such as interleukin (IL)-1β, IL-6, tumor necrosis factor-α, and monocyte chemoattractant protein-1.…”
Section: Fig 2 Long-term Effect (5 Participants)mentioning
confidence: 99%
“…As a result, the GAGs (933±175 mg per 10 6 cells) and collagen (436±85 mg per 10 6 cells) yield at week 3 ( Figure 6b) excelled compared to those of cartilaginous tissues cultured in other reactors for longer periods of time. [28][29][30][31] Cartilage repair can be accelerated by in vivo gene therapy, which is simple and effective. 32 However, efficient transduction of chondrocytes is hindered by the dense surrounding ECM and direct vector injection may elicit strong inflammatory responses, which interfere with the reparative process.…”
Section: Discussionmentioning
confidence: 99%